Celebrating Stonewall at 50: A Culturally Geographic Approach to Introducing LGBT Themes. Issue 1 (2nd January 2019) - Varga, Bretton A.; Beck, Terence A.; Thornton, Stephen J.
Abstract: July 28, 2019, marks the 50th anniversary of a police raid on the Stonewall Inn. During this raid, police verbally, and in some cases, physically accosted patrons of the Stonewall Inn. Events from this encounter eventually set off a series of protests by members and allies of the LGBT community. These protests came to be known as the Stonewall Riots. On June 24, 2016, the Stonewall Inn became the first U.S. National Monument dedicated to LGBT history. While this event served as a pivotal role in the gay rights movement, this article begins with an investigation into the geographical and spatial conditions surrounding the Stonewall Inn and its neighborhood. In asking, "Why New York City, why Stonewall?" we attempt to establish a cultural version of geography that uses a National Monument as a way for students to engage in the world around them through an examination of human/environment relationships. To explore this further and to celebrate Stonewall at 50, we present a pedagogical framework using articles, letters, photographs, podcasts, and Google Earth.